Pembuatan Etanol Dari Nira Tebu Dengan Metode Fermentasi - Rohmatun Nafi'ah; Susan Prima Devi (Cendekia Journal of Pharmacy, 2019)
Tebu is one of the many plants found in the Holy area of Central Java, which has a high sugar content. The raw material for making ethanol is sugary, starchy and fibrous. Nira is one of the by-products of a sugar cane factory which has a high sugar content. The study of making ethanol from Nira Tebu as a raw material for medicine using fermentation methods was carried out on a laboratory scale. The purpose of this study was to produce ethanol from Nira Tebu as a raw material for chemical drugs by fermentation method.The procedure of this study was through the pretreatment stage, the hydrolysis stage, and the fermentation stage. The fermentation process with the addition of yeast and lasts for 7 days with the volume of sugarcane juice used is 5 liters. Yeast used for fermentation is 1,2,3,4 and 5 grams and varies from 1-7 days of fermentation time. Furthermore, ethanol levels and acidity levels (pH) were determined from Nira Tebu. So that from the results of the study it can be obtained the most optimal ethanol levels with variations in the amount of yeast and the length of fermentation time.